Evaluating Risk Factors for Early-onset Neonatal Sepsis - Iskandar, Wedi; Juniartho, Rizky Dwi; Triyani, Yani; Permatagalih, Vidi (Global Medical & Health Communication (GMHC), 2024)
Neonatal sepsis is a systemic infection that occurs in infants at 28 days of life and is a significant cause of morbidity and death in newborns. Early-onset neonatal sepsis (EONS) occurs within 72 hours after birth and is often associated with infections contracted before or during childbirth. The study aims to evaluate the risk factors of EONS. The study design was a case-control retrospective observational study that evaluated the medical records of neonates who were admitted to the neonatal care unit of Al Islam Hospital Bandung from January 2020 to December 2022. This study assessed the impact of independent variables such as gestational age, birth weight, premature rupture of membrane (PROM), miconeal amniotic fluid, APGAR score of 5 minutes, and the mother's white blood cell count elevation (>15,000/µl). The logistic regression analyses were employed to analyze the data. The logistic regression analyses were employed to analyze the data. The study included 3,103 neonates, of whom 124 met the inclusion criteria. Thirty-nine patients (31.35%) were diagnosed with sepsis, while 85 patients (68.55%) did not have sepsis. Based on bivariate analysis, EONS was significantly linked to low birth weight (p=0.027, 95% CI=0.184 to 0.902, OR=2.455), PROM (p=0.000, 95% CI=4.359 to 26.582, OR=10.764), and the mother's white blood cell count elevation (p=0.002, 95% CI=1.560 to 7.622, OR=3.448). On multivariate analysis, the risk factors were significantly associated (p<0.05), which had an influence of 38.4% on EONS (Nagelkerke R square=0.384). In conclusion, the risk factors for EONS were low birth weight, PROM, and elevation of white blood cell count in the mother, which increased by 38.4% with EONS.